The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00004872-200205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide system in fetal heart and circulation

Abstract: Atrial natriuretic peptide, brain natriuretic peptide and C-type natriuretic peptide belong to a family of hormones that have diuretic, natriuretic and vasodepressor activity and play a part in pressure and volume homeostasis in adults. As little is known about the natriuretic peptides during cardiac maturation, this review summarizes current knowledge about the early expression of components of the natriuretic peptide system in the heart during embryonic and fetal development. The data indicate a functional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 65 publications
2
13
0
1
Order By: Relevance
“…As reported by Walther et al (29), the natriuretic peptides appear to respond to similar stimuli, and to perform similar cardiovascular functions during development as they do in adults. The fetal natriuretic peptides (30,31) can react to volume loading, hyperosmolality, and vasoconstrictors Ang II, phenylephrine, and endothelin in a manner similar to that in the adult heart; however, ANP and BNP respond differently to short-term and long-term volume load in the fetal circulation (32).…”
Section: Fetal Natriuretic Peptidessupporting
confidence: 55%
“…As reported by Walther et al (29), the natriuretic peptides appear to respond to similar stimuli, and to perform similar cardiovascular functions during development as they do in adults. The fetal natriuretic peptides (30,31) can react to volume loading, hyperosmolality, and vasoconstrictors Ang II, phenylephrine, and endothelin in a manner similar to that in the adult heart; however, ANP and BNP respond differently to short-term and long-term volume load in the fetal circulation (32).…”
Section: Fetal Natriuretic Peptidessupporting
confidence: 55%
“…Histological and immunocytochemical studies, as well as in situ hybridization analysis, confirmed expression of the ANP gene in human [32] and ovine fetal heart [33]. Moreover, whereas ANP [34] and ANP mRNA [35] are present throughout the heart in the early embryological stages of development, the ventricular representation regresses markedly towards the later developmental phases [35] (for review see [36]). Mature ANP is a 28-amino-acid peptide hormone with a molecular mass of 3080.5 kDa (C 127 H 203 N 45 O 39 S 3 ).…”
Section: Anp: a Cardiac Hormonementioning
confidence: 79%
“…5A,C,E) (Moorman and Christoffels, 2003). Nppa is a hormone involved in the homeostatic regulation of blood pressure and volume in adults (Walther et al, 2002). Previous reports have shown that Tbx2 downregulates expression of an Nppa reporter in transgenic mouse embryos at 10.5 dpc (Habets et al, 2002).…”
Section: Myocardial Differentiation and Patterning In Tbx2 Tm1pamentioning
confidence: 99%